The 12/15-lipoxygenase pathway promotes osteoclast development and differentiation - Krönke, Gerhard; Uderhardt, Stefan; Katzenbeisser, Julia; Schett, Georg (Autoimmunity, 2009)
Although 12/15-lipoxygenase (12/15-LO) has been implicated as negative regulator of systemic bone mass in mice and humans, the underlying mechanisms remain elusive. Here, we show that 12/15-LO is a positive regulator of osteoclast (OC) development. Enzymatic inhibition as well as genetic ablation of 12/15-LO significantly impaired osteoclastogenesis. Conversely, addition of the 12/15-LO-derived eicosanoids 12- and 15-HETE augmented differentiation of precursors into fully matured OCs. Together these data point towards a crucial role of 12/15-LO in the regulation of OC development. Therefore, 12/15-LO and its human homologue 15-LO may display novel targets for the treatment of diseases such as osteoporosis and rheumatoid arthritis. © 2009 Informa UK Ltd All rights reserved.
CRIS-Team Scopus Importer:2020-11-20
Keywords: 12/15-LO; HETE; OC